2022
DOI: 10.3390/biomedicines10071586
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation of the Human Dental Pulp Induces Phosphorylation of eNOS at Thr495 in Blood Vessels

Abstract: The activity of endothelial nitric oxide synthase (eNOS) in endothelial cells increased with the phosphorylation of the enzyme at Ser1177 and decreased at Thr495. The regulation of the phosphorylation sites of eNOS at Ser1177 and Thr495 in blood vessels of the healthy and inflamed human dental pulp is unknown. To investigate this, healthy and carious human third molars were immersion-fixed and decalcified. The localization of eNOS, Ser1177, and Thr495 in healthy and inflamed blood vessels was examined in conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…However, during inflammation, sGC is oxidized (from Fe 2+ to Fe 3+ ) by higher concentrations of O 2 − and ONOO − , leading to the insensitivity of sGC to NO [ 3 , 4 , 5 , 6 ]. Inflammation induces an increase in ROS and RNS concentrations [ 71 , 72 ]; this effect has been reported for inflamed dental pulp [ 49 , 50 ]. In addition, the inflammation-dependent synthesis of ROS and RNS in mast cells has also been described [ 70 ].…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…However, during inflammation, sGC is oxidized (from Fe 2+ to Fe 3+ ) by higher concentrations of O 2 − and ONOO − , leading to the insensitivity of sGC to NO [ 3 , 4 , 5 , 6 ]. Inflammation induces an increase in ROS and RNS concentrations [ 71 , 72 ]; this effect has been reported for inflamed dental pulp [ 49 , 50 ]. In addition, the inflammation-dependent synthesis of ROS and RNS in mast cells has also been described [ 70 ].…”
Section: Discussionmentioning
confidence: 90%
“…In inflammation, O 2 − and ONOO − oxidize sGC (Fe 2+ to Fe 3+ in the β 1 subunit of sGC), leading to the insensitivity of sGC to NO [ 3 , 4 , 5 , 6 ]. Because O 2 − and ONOO − have been detected at higher concentrations in inflamed dental pulp [ 49 , 50 ], we suggested that sGC might be present as an α 1 β 1 isoform in mast cells at the protein level and could be insensitive to NO in the oxidized state in these cells during the inflammation of human dental pulp.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations